The secret lives of wedgefish: first insights into fine-scale behaviour and movement ecology of a globally imperilled ray - Karissa O. Lear; Carlos Estrabeau; David L. Morgan; Nicholas M. Whitney; Adrian C. Gleiss; Colby Bignell; Richard D. Pillans; Rebecca L. Bateman (Marine Biology, 2024)
Wedgefishes have recently been recognised as one of the most imperilled marine fish families worldwide. However, many knowledge gaps about their biology and ecology hinder conservation efforts. Here we used a combination of acoustic telemetry and acceleration datalogger technology to gain fundamental insights into the fine-scale behaviour, habitat use, size of activity spaces, and residency of adult female bottlenose wedgefish ( Rhynchobatus australiae ) in the Ningaloo region of northwestern Australia. Acoustic tracking data over one year demonstrated that female bottlenose wedgefish continuously resided in a relatively small area of a productive coral reef lagoon. Acceleration data revealed that bottlenose wedgefish were nocturnal, with time of day having a greater influence on activity than tidal patterns. Bottlenose wedgefish also increased activity with seasonally increasing temperatures. We identified several discrete behavioural signatures in the acceleration data, inferred to correspond to chafing, settling/burying behaviour, foraging behaviour, and escape behaviour, based on their kinematics. Further observations are required to confirm these behaviours with certainty. Additionally, according to datalogger and acoustic data, tagged bottlenose wedgefish rarely inhabited areas greater than 2 m deep. Together, these first insights into behaviour and habitat use of adult female bottlenose wedgefish highlight the importance of nearshore habitats for this species and indicate that they may be highly resident to specific areas. Our findings provide important insight into the conservation of bottlenose wedgefish in northwestern Australia, including potential effectiveness of protected areas and interactions with specific anthropogenic threats such as shoreline development and recreational beach fishing.